Mapping impacts of open innovation practices in a firm competitiveness - Alex Fabianne de Paulo (Journal of Technology Management & Innovation, 2017)
This manuscript aims to understand how it is possible to improve the competitiveness of a company using open innovation practices and presents evidences that open innovation can be practice, especially regarding technologies adoption and actions involving partnerships and collaboration. The paper concludes, base in a case study of a ICT firm, that even with a partial degree of openness and an intermediate level of maturity, open innovation put into practice have contributed to technological development and increase company competitiveness in its activity sector. It also pointed out challenges in execution capacity, internal process improvements and partnership relations, but mainly challenge is breaking cultural barriers in open innovation implementation. Finally, a set of recommendations were proposed to expand actions based on open innovation management, upgrade innovation maturity level and increase competitive potential of the companies.